Nanotechnology for Energy and Water Proceedings of the International Conference NEW-2017 (Springer Proceedings in Energy,, 2018)
This volume originates from the proceedings of the International Conference on Nano for Energy and Water (NEW) & Indo French Workshop on Water Networking, 22-24 February, 2017 in Dehar. NEW-2017 is aimed at students, educators, researchers, scientists, engineers and industrialists, engaged in a wide range of nanotechnology fields and related applications. NEW-2017 will provide an ideal environment to develop new collaborations and meet experts of thematic areas. The conference aims to exchange the technical/scientific information with the representatives of various industries and R & D Organisations, to provide technical support to government and non-government agencies across the globe in policy planning and implementation in the relevant areas, to promote and document the recent developments in nanotechnology for energy and water applications and to highlight the future need of nanotechnology in different fields.